Comparative study of biorefinery processes for the valorization of fast-growing Paulownia wood - del Río, Pablo G. (2020)
In this work, valorization of Paulownia wood (PW) was proposed following several process configurations for biofuels and value-added compounds production. Firstly, autohydrolysis and ethanol-organosolv strategies were assessed separately for the fractionation of PW to enhance the enzymatic digestibility of cellulose. A third strategy focused on a sequential process (autohydrolysis and organosolv) was explored. Two temperatures were selected for the first stage of the combined process. High concentration of oligosaccharides (26.29 g/L) and high concentration of degradation products (17.21 g/L) were obtained at 210 and 230 °C, respectively. The solids obtained from both pretreatments were subjected to organosolv delignification (200 °C, 3 h and 50% ethanol) achieving delignification of 58 and 30% for the autohydrolyzed biomass at 210 °C and 230 °C, respectively. The combined process resulted in susceptible biomass able to produce 64 g/L of ethanol. Therefore, the strategies explored in this work open the possibility to build a refinery around Paulownia wood.